A comparative study of 70 cases of inter-trochanteric fracture femur treated with dynamic hip screw and proximal femoral nailing - Singla, Gaurav (International Journal of Research in Orthopaedics, 2017)
Background: Inter-trochanteric fracture femur is a common and grievous injury, mostly suffered in elderly people. It accounts for approximately half of hip fractures in elderly and out of this, more than 50% of fractures are unstable. In old age, it occurs mostly due to trivial trauma. Various procedures of internal fixation had been proposed as a treatment. DHS considered to be the standard procedure for comparison of outcomes. The advantage of proximal femur nailing fixation is that it provides a more biomechanically stable construct by reducing the distance between hip joint and implant. The goal of this study is to compare the clinical and radio-graphical results of the DHS and PFN for the treatment of Intertrochanteric hip fractures (load bearing vs. load sharing). Methods: Seventy patients (more than 55 years old) presented to Adesh Hospital from March 2015 to November 2015 with trochanteric fracture femur. Patients were treated with osteosynthesis with dynamic hip screw (DHS) and proximal femoral nailing (PFN). The clinical results were compared between the dynamic hip screw and proximal femoral nailing groups of 35 patients each. All surgeries done on traction table and were followed up at regular intervals of 4 weeks, 6 weeks, 8 weeks, 10 weeks, 12 weeks, 6 months and at 1 year. Results: We observed no statistically significant difference between two groups in view of late & early complications and time to union. We observed significantly better outcomes in PFN group for unstable inter-trochanteric fractures and in unstable fractures reduction loss is significantly lower in PFN group. Conclusions: We concluded that PFN may be the better fixation device for most unstable inter-trochanteric fractures.